What Lies Beyond – The Frontier and the Creation of the Monstrous - Marko Lukić ([sic])
Space represents a crucial component in the process of analyzing and understanding literature and the various cultural implications that literature is more often than not exposed to. This is particularly true when the subject of the analysis is American literature whose origins, and its later development through the years, represent a constant interchanging and merging of numerous cultural and social values. The spatial aspect and its influence on American literary production constantly develops, much like the country and its literary focus, adapting to the ever-changing world. Therefore the aim of this analysis cannot be an attempt to provide an overview of the numerous instances of interaction that have taken and still are taking place between literature, or its authors, and the various notions and ideas of space as defined by disciplines such as human geography. Instead, what this particular analysis can do is to provide insight into a type of “space” both extremely specific to the American experience and in many ways a constant presence within numerous American creative processes. It is the concept of the “Frontier” that positions itself as a key notion that defines many aspects of both the American imaginary and the real, and which as the analysis will show, is not limited to a defined historical or cultural context, but instead functions as a continuous source of inspiration and national/personal introspection.